Epidemiological insights into HIV-related discrimination in Indonesia and Myanmar: Evidence from DHS Phase 7 (Al-Sihah : The Public Health Science Journal, 2025)
Despite expanded HIV awareness efforts, comparable evidence on the determinants of discriminatory attitudes in Southeast Asia remains limited. This study explored the key factors contributing to stigma and discriminatory attitudes toward people living with HIV (PLWH) in Indonesia and Myanmar, utilizing data from the Demographic and Health Survey (DHS) Phase 7. A total of 57,409 individuals participated in the analysis—41,592 from Indonesia and 15,817 from Myanmar. Attitudes were assessed based on responses to statements about school participation and buying food from PLWH. The dataset was weighted to ensure national representation. Statistical analysis involved chi-square tests followed by multivariate logistic regression. In Indonesia, variables such as age, sex, residence, and HIV-related knowledge were significantly associated with discriminatory attitudes. Women and individuals in rural areas were more likely to express stigma. In both countries, higher knowledge about HIV was linked to lower discrimination. Gender emerged as the strongest predictor in Indonesia, while geographic location was more influential in Myanmar. These results underscore the importance of tailored strategies, including gender-responsive education, awareness initiatives focused on rural populations, and policy reforms aimed at reducing stigma and fostering greater acceptance of PLWH.